PENGARUH MODEL STEM TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA PADA PEMBELAJARAN IPA - Sheila Shabrina Shabrina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the STEM (Science, Technology, Engineering, and Mathematics) learning model on students’ critical thinking skills in science learning for fifth-grade elementary students. This research is motivated by the low critical thinking skills of students, which are indicated by learning activities that are still conventional and teacher-centered. The method used in this study is a quasi-experimental method with a nonequivalent control group design. The research subjects consisted of two classes: the experimental class, which used the STEM model, and the control class, which used conventional learning. Data were collected through a critical thinking test developed based on Facione’s indicators, including interpretation, analysis, evaluation, inference, explanation, and self-regulation. The data obtained were analyzed descriptively and inferentially using the Mann–Whitney test to examine the difference in the improvement of critical thinking skills between the two classes. The results showed a significant improvement in students’ critical thinking skills after the implementation of the STEM learning model. The average posttest score of the experimental class was higher than that of the control class, with an increase from 52.4 to 75.6. This improvement covered all critical thinking indicators, particularly in the aspects of analysis and inference. Based on these findings, it can be concluded that the application of the STEM model has a positive effect on improving students’ critical thinking skills in science learning, making it an innovative alternative to enhance the quality of 21st-century learning in elementary schools. Keywords: STEM model, critical thinking skills, elementary school students. Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran STEM (Science, Technology, Engineering, and Mathematics) terhadap keterampilan berpikir kritis siswa pada pembelajaran IPA di kelas V Sekolah Dasar. Penelitian ini dilatarbelakangi oleh rendahnya keterampilan berpikir kritis siswa yang ditunjukkan melalui pembelajaran yang masih bersifat konvensional dan berpusat pada guru. Metode yang digunakan dalam penelitian ini adalah kuasi eksperimen dengan desain nonequivalent control group design. Subjek penelitian terdiri dari dua kelas, yaitu kelas eksperimen yang menggunakan model STEM dan kelas kontrol yang menggunakan pembelajaran konvensional. Teknik pengumpulan data dilakukan melalui tes berpikir kritis yang dikembangkan berdasarkan indikator Facione, meliputi interpretasi, analisis, evaluasi, inferensi, penjelasan, dan pengaturan diri. Data yang diperoleh dianalisis secara deskriptif dan inferensial menggunakan uji Mann-Whitney untuk melihat perbedaan peningkatan keterampilan berpikir kritis antara kedua kelas. Hasil penelitian menunjukkan bahwa terdapat peningkatan yang signifikan pada keterampilan berpikir kritis siswa setelah diterapkannya model pembelajaran STEM. Rata-rata nilai posttest kelas eksperimen lebih tinggi dibandingkan dengan kelas kontrol, dengan peningkatan rata-rata dari 52,4 menjadi 75,6. Peningkatan tersebut mencakup seluruh indikator berpikir kritis, terutama pada aspek analisis dan inferensi. Berdasarkan hasil tersebut, dapat disimpulkan bahwa penerapan model STEM berpengaruh positif terhadap peningkatan keterampilan berpikir kritis siswa pada pembelajaran IPA, sehingga model ini dapat dijadikan alternatif inovatif dalam upaya meningkatkan kualitas pembelajaran abad ke-21 di sekolah dasar. Kata kunci: Model STEM, keterampilan berpikir kritis, siswa sekolah dasar